Technology-supported classroom and its impacts on teachers’ roles / Evelyn Sharminnie S. Vasuthavan - S. Vasuthavan, Evelyn Sharminnie (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2018)
One of the main characteristics of education in the 21st century is the incorporation of technology in teaching and learning. Apart from its ability to make teaching and learning more convenient, efficient and effective, technology is also crucial for equipping learners with the necessary skills to survive in the current world. The Malaysian Ministry of Education has spent more than RM6 billion on Information and Communication Technology (ICT) over the past decade for education initiatives (Malaysian Education Blueprint, 2013) to scale up quality learning and increase exposure towards technology- based tools, in order to produce manpower whose skills and knowledge is relevant to the dynamic global era. Hence, the emergence of technology-supported classroom. According to Dorota Domalewska (2014), a technology-supported classroom is a classroom that incorporates technology like Web 2.0 tools to address learning outcomes. From blogs and wikis to video sharing and social networking, these technological tools allow active and interconnected processing, digestion and evaluation of information, which is the goal of a technology-supported classroom. McGhee & Kozma (n.d.) addresses the technology-supported classroom as a classroom that uses educational technology to provide students with tools and information that support problem solving, communication, collaboration, and knowledge creation. Technology-supported classroom has produced a significant gap between conventional approaches and new technology-supported approaches, which in turn has greatly impacted the role of teachers.